Numerical Simulations on Mixing Dynamics of Spherical and Non-Spherical Tablets in a Pan Coater - Chand, R.; Hadj Lajimi, R.; Uddin, S.; Meghwar, S.; Farooq, U.; Rekik, N. (Engineering, Technology & Applied Science Research, 2019)
Discrete element simulations provide valuable insight into the mixing dynamics of granular materials in industry. In this paper, numerical work is conducted in order to find the influence of pan rotational velocity and particle shape on mixing behavior. Four types of particles of different shapes were chosen: spherical, non-spherical type 1 (disk shape), non-spherical type 2 (capsule shape), and non-spherical type 3 (triangular shape). The pan mixer was filled with 30 % volume of the same shape with the particles and was rotated at 15 RPM, 30 RPM, 45 RPM, and 60 RPM. The particles were colored as bottom-particles, middle-particles, and top-particles in order to visualize mixing efficiency. The homogeneity of the mixtures was determined by using contact dynamics of particles. The results show that fast-rotating pan (30-60 RPM) provides good mixing for all shapes of particles. However, non-spherical particles do not show as good mixing as spherical particles.